The world is round - Stein, Gertrude, 1874-1946; Hurd, Edith Thacher, 1910-1997. (New York : Harper Design, 2013)
Rose wonders who she is, asking herself if she would still be Rose if her name were not Rose, and goes on a journey in search of herself.
Afterword, titled The world is not flat, originally published in 1986 by Arion Press, San Francisco.
boek
Keywords: Children's stories; Identity -- Juvenile fiction; Hurd, Clement